2019
DOI: 10.1136/vr.l6563
|View full text |Cite
|
Sign up to set email alerts
|

Are low doses of oral glucocorticoids as effective as high doses as the sole treatment for canine pemphigus foliaceus?

Abstract: • The management of canine pemphigus foliaceus is challenging because the skin condition does not always respond to therapy, and this may lead to euthanasia. Furthermore, dogs will often show signs of adverse reactions to medication. Therapy usually relies on oral steroids, often in combination with adjunct therapies, although the effectiveness of the latter remains difficult to ascertain. • The use of oral glucocorticoids at an initial dose of 2 mg/kg/day may prove effective in some cases. In the long term, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…The benefit of pulse therapy over conventional daily GC dosing was not apparent in a small case series of 12 cats with PF 31 . In a critically appraised topic on the dosage of prednisone or prednisolone for the treatment of canine PF, there was no compelling evidence that oral prednisone or prednisolone at the dose of 2 mg/kg/day was effective in induction and/or maintenance of CR, and the authors suggested that a higher dose is more likely to be associated with CR 32 . Likewise, high doses of oral GCs (≥3 mg/kg/day for dogs and ≤3 mg/kg twice daily for cats)—often in combination with another immunosuppressant—have been recommended for the treatment of canine and feline PV, 33 and canine uveodermatological syndrome (UDS) 34 .…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…The benefit of pulse therapy over conventional daily GC dosing was not apparent in a small case series of 12 cats with PF 31 . In a critically appraised topic on the dosage of prednisone or prednisolone for the treatment of canine PF, there was no compelling evidence that oral prednisone or prednisolone at the dose of 2 mg/kg/day was effective in induction and/or maintenance of CR, and the authors suggested that a higher dose is more likely to be associated with CR 32 . Likewise, high doses of oral GCs (≥3 mg/kg/day for dogs and ≤3 mg/kg twice daily for cats)—often in combination with another immunosuppressant—have been recommended for the treatment of canine and feline PV, 33 and canine uveodermatological syndrome (UDS) 34 .…”
Section: Glucocorticoidsmentioning
confidence: 99%